(untitled) (London Journal of Research In Management & Business, 2025)
The research Measuring the Costs of Faculty Turnover and Teacher Absenteeism and Their Implications for the Performance of Higher Education Institutions aims to demonstrate the costs arising from turnover at the Faculty of Economics, University 11 de Novembro (FEUON). This study is relevant for institutional management as it allows the identification of dysfunctions that undermine organisational efficiency and financial sustainability. It is a descriptiveexploratory study with a qualitative approach, conducted through field research. Data collection was carried out using semi-structured interviews applied to the heads of the Human Resources, Financial, and Scientific departments, as well as to the teaching and research units, including both active and former faculty members. The information was analysed using statistical techniques that enabled the explanation of the causeeffect relationship between faculty turnover and absenteeism and the costs incurred by the institution. The findings revealed hidden costs amounting to AOA 6,501,607.20, most of which were intangible and identified through the application of the SOF Method. It was observed that faculty turnover not only increases the visible cost structure but also results in productivity loss, disruption of the teachinglearning process, and organisational demotivation, thereby compromising academic quality and institutional performance. The analysis, grounded in socio-economic and behavioural theory, demonstrates that the absence of effective policies for the retention and appreciation of human capital raises hidden costs, undermining the competitiveness and sustainability of FEUON in the medium and long term.